The 1000 Chinese Indigenous Pig Genomes Project provides insights into the genomic architecture of pigs - Heng Du; Lei Zhou; Zhen Liu; Yue Zhuo; Meilin Zhang; Qianqian Huang; Shiyu Lu; Kai Xing; Li Jiang; Jian-Feng Liu (Nature Communications)
Abstract Pigs play a central role in human livelihoods in China, but a lack of systematic large-scale whole-genome sequencing of Chinese domestic pigs has hindered genetic studies. Here, we present the 1000 Chinese Indigenous Pig Genomes Project sequencing dataset, comprising 1011 indigenous individuals from 50 pig populations covering approximately two-thirds of China’s administrative divisions. Based on the deep sequencing (~25.95×) of these pigs, we identify 63.62 million genomic variants, and provide a population-specific reference panel to improve the imputation performance of Chinese domestic pig populations. Using a combination of methods, we detect an ancient admixture event related to a human immigration climax in the 13th century, which may have contributed to the formation of southeast-central Chinese pig populations. Analyzing the haplotypes of the Y chromosome shows that the indigenous populations residing around the Taihu Lake Basin exhibit a unique haplotype. Furthermore, we find a 13 kb region in the THSD7A gene that may relate to high-altitude adaptation, and a 0.47 Mb region on chromosome 7 that is significantly associated with body size traits. These results highlight the value of our genomic resource in facilitating genomic architecture and complex traits studies in pigs.